IMPLEMENTATION OF PROJECT BASED LEARNING THROUGH CREATING POP UPS SOLAR SYSTEM TO IMPROVE STUDENT’S DIGITAL SCIENCE LITERACY - Nugroho, Agung Nur; Wilujeng, Insih; Rahmawati, Laifa (Universitas Bhinneka PGRI, 2025)
This study aims to determine the effectiveness of the application of project-based learning in creating pop ups solar system to improve digital science literacy and to know the difference in the average score of digital science literacy ability improvement before and after the application of project-based learning in creating pop ups solar system. The research design used is one group pretest-posttest design with descriptive statistical analysis techniques, normality test (Shapiro-Wilk), Paired Sample T-Test, N-Gain, and qualitative analysis. The results of data analysis showed that there was a significant increase in students' digital science literacy skills with a moderate category and a significant increase in the average score of students' digital science literacy skills before and after the application of project based learning in creating solar system pop ups